Nanoscale cathodoluminescence of stacking faults and partial dislocations in a‐plane GaN. Issue 1 (16th September 2015) - Schmidt, Gordon; Veit, Peter; Wieneke, Matthias; Bertram, Frank; Dadgar, Armin; Krost, Alois; Christen, Jürgen
Abstract : In GaN, the basal plane stacking fault type I1 is a two‐dimensional defect characterized by a cubic inclusion within the wurtzite structure. Excitons are bound at the BSF I1 similar to the localization in a quantum well heterostructure leading to an efficient radiative recombination. In this study, we present the optical and structural properties of basal plane stacking faults occurrent in silicon doped a ‐plane GaN layer by means of highly spatially resolved cathodoluminescence spectroscopy performed in a scanning transmission electron microscope. Drastically reduced panchromatic intensity in the vicinity of partial dislocations terminating the stacking faults, points to their non‐radiative character. Originating from intersection of two‐dimensional defects, the emission at 379.6 nm could be attributed to optically active stair‐rod dislocations.